2010
DOI: 10.1007/s00125-010-2000-9
|View full text |Cite
|
Sign up to set email alerts
|

Delayed intervention with AGE inhibitors attenuates the progression of diabetes-accelerated atherosclerosis in diabetic apolipoprotein E knockout mice

Abstract: Aims/hypothesis Formation of AGEs is increased in the diabetic milieu, which contributes to accelerated atherogenesis. We studied whether delayed treatment with AGE-inhibiting compounds, alagebrium chloride and pyridoxamine dihydrochloride, affected established atherosclerosis in experimental diabetes in comparison with the angiotensin-converting enzyme inhibitor, quinapril. Methods Streptozotocin-induced diabetic male Apoe −/− mice (n=24 per group) received, by oral gavage, from week 10 to 20 of diabetes: no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 22 publications
6
41
0
Order By: Relevance
“…Collagen is a critical component of atherosclerotic lesions [8,32]. In the present study, increased aortic gene expression of collagens I and III was observed in diabetic global ApoE − / − mice, which is consistent with our previous studies [2,8].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Collagen is a critical component of atherosclerotic lesions [8,32]. In the present study, increased aortic gene expression of collagens I and III was observed in diabetic global ApoE − / − mice, which is consistent with our previous studies [2,8].…”
Section: Discussionsupporting
confidence: 95%
“…Extracellular matrix proteins and MMPs are critical components of atherosclerotic lesions [8,32]. The stability of an atherosclerotic plaque depends on the interplay between collagens, which provide plaque stability, and MMPs, which degrade collagen and extracellular matrix, potentially weakening the plaque.…”
Section: Expression Of Collagens and Mmps (Matrix Metalloproteinases)mentioning
confidence: 99%
“…Several AGE-lowering compounds have been shown to reduce atherosclerosis in animal models (4,5), demonstrating that AGEs are no innocent bystanders and are of importance for the development of CVD.…”
mentioning
confidence: 99%
“…One key pathway is the increased production of reactive dicarbonyls generated from triose phosphate intermediates of glycolysis, glycerol and ketone peroxidation, overactivation of the polyol pathway, and the degradation of glycated proteins (3)(4)(5)(6). In experimental diabetes, circulating and tissue levels of methylglyoxal (MG) are three to five times higher than in the nondiabetic state (7,8). Plasma MG concentrations are also elevated in patients with diabetes (9), especially those with vascular complications (10).…”
mentioning
confidence: 99%
“…Carbonyl-derived AGEs have been detected within atherosclerotic lesions in both extra-and intracellular locations and correlate with the size, complexity, and stability of the lesions (12,13). The potential importance of a-dicarbonyls in the pathogenesis of glucose-dependent atherogenesis is illustrated by the vasculoprotective effects of dicarbonyl scavengers in diabetes, in the absence of euglycemia (7,14).…”
mentioning
confidence: 99%